New insights into the role of dietary spermine on inflammation, immune function and related-signalling molecules in the thymus and spleen of piglets. Issue 3 (4th May 2017) - Cao, Wei; Wu, Xianjian; Jia, Gang; Zhao, Hua; Chen, Xiaoling; Wu, Caimei; Tang, Jiayong; Wang, Jing; Cai, Jingyi; Liu, Guangmang
ABSTRACT: This study aimed to determine the effects of dietary spermine supplementation on the inflammatory response and immune function of the thymus and spleen in piglets. Eighty suckling piglets were randomly assigned to receive adequate nutrients supplemented with spermine (0.4 mmol/kg body weight) or restricted nutrient intake supplemented with normal saline for 7 h or 3, 6 and 9 days in pairs. Regardless of treatment time, spermine supplementation decreased ( p  < 0.05, compared with the controls) the following: (1) tumour necrosis factor α (TNF-α), interleukin (IL)-1β, 2 and 6, and interferon (IFN)-γ levels in serum; (2) gene expression of cluster of differentiation 8 and integrin beta-2 in the thymus and spleen and the lymphocyte function-associated antigen 1 in the thymus; (3) mRNA levels of TNF-α, IL 1β, 2, 6, and 12, IFN-γ and inducible nitric oxide synthase in the thymus and spleen, as well as IL-8 in the spleen; and (4) eukaryotic IF4E-binding protein 1, Janus kinase 2, signal transducer and activator of transcription 3, and nuclear factor-kappa B P65 gene transcriptions in the thymus and spleen. By contrast, spermine supplementation increased ( p  < 0.05) the following: (1) immunoglobulin M, IL-10, and transforming growth factor β1 gene expression, as well as (2) relative mRNA levels of mammalian target of rapamycin (mTOR) and ribosomal protein S6 kinase 1 in the thymus and spleen. These effects were also observed upon prolonged spermine administration ( p  < 0.05). In summary, dietary spermine supplementation can alleviate inflammatory response, enhance the immune function and regulate the gene expression of signalling molecules related to inflammation.